The adoption of the Reference Framework for diabetes care among primary care physicians in primary care settings: A cross-sectional study. Issue 31 (August 2016) - Wong, Martin C.S.; Wang, Harry H.X.; Kwan, Mandy W.M.; Chan, Wai Man; Fan, Carmen K.M.; Liang, Miaoyin; Li, Shannon TS; Fung, Franklin D.H.; Yeung, Ming Sze; Chan, David K.L.; Griffiths, Sian M.
Abstract : Abstract: The prevalence of diabetes mellitus has been increasing both globally and locally. Primary care physicians (PCPs) are in a privileged position to provide first contact and continuing care for diabetic patients. A territory-wide Reference Framework for Diabetes Care for Adults has been released by the Hong Kong Primary Care Office in 2010, with the aim to further enhance evidence-based and high quality care for diabetes in the primary care setting through wide adoption of the Reference Framework. A valid questionnaire survey was conducted among PCPs to evaluate the levels of, and the factors associated with, their adoption of the Reference Framework. A total of 414 completed surveys were received with the response rate of 13.0%. The average adoption score was 3.29 (SD 0.51) out of 4. Approximately 70% of PCPs highly adopted the Reference Framework in their routine practice. Binary logistic regression analysis showed that the PCPs perceptions on the inclusion of sufficient local information (adjusted odds ratio [aOR] = 4.748, 95%CI 1.597–14.115, P  = 0.005) and reduction of professional autonomy of PCPs (aOR = 1.859, 95%CI 1.013–3.411, P  = 0.045) were more likely to influence their adoption level of the Reference Framework for diabetes care in daily practices. The overall level of guideline adoption was found to be relatively high among PCPs for adult diabetes in primary care settings. The adoption barriers identified in this study should be addressed in the continuous updating of the Reference Framework. Strategies need to be considered to enhance the guideline adoption and implementation capacity.